What is Nikolai Klyuev’s “Hung Upside Down” Crying for? (On Poetic Epitaph to Victims of White Terror) - I. V. Kudryashov (Tsentr nauchnykh i obrazovatelnykh proektov, 2021)
The article is devoted to the problems of historical and cultural commentary, as well as the interpretation of the ideological-figurative content and genre attribution of N. A. Klyuev’s poem “Hung upside down...”, created by the poet during the Vytegorsk period of his life (1918—1922). The analysis showed that the facts of Klyuev’s Vytegorsk life at the time of his creation “Hung upside down...” and the poet's deeply felt fear of being subjected to a cruel execution prompted him to literally perpetuate the memory of the victims of the White Terror who were martyred by hanging during the Civil War. The authors of the study come to the conclusion that references to the Bible and L. I. Palmin’s poem “Requiem” make it possible to attribute this work of Klyuev to one of the most ardent works of the poet of that time, calling on the living to selflessly serve the ideals of the proletarian revolution, and to identify its genre as a literary epitaph to the victims of the White Terror, which stands out for its monumentality and the timelessness of its valuable message to descendants. The authors of the article are convinced that the failed attempt by Klyuev to republish the poem “Hung upside down...” in 1927 betrays the poet, who is experiencing criticism of the counter-revolutionary content of his works, a desire to demonstrate the continuity of his later work with his “communard” past.